Antecedentes en chile de enfermedades virales de los animales domésticos. II. Enfermedades de presentación cíclica y de alta seroprevalencia - Berrios E., Patricio (Avances en Ciencias Veterinarias, 2002)
In this general article is presented background information on domestic animal viral diseases in Chile of cyclic presentation like equine influenza and equine rhinopneumonitis and of high seroprevalence like infection bovine rhinotracheitis, bovine viral diarrhea/mucosal disease, bovine and ovine parainfluenza type 3, porcine parvovirosis and ovine bluetongue. Emphasis is given in Chilean research carried out from 1960. This article continues the background information presented in a previous general article mainly refered to erradicated viral diseases from Chile like foot-and-mouth disease, hog cholera and equine infectious anemia, and viral diseases under control like rabies and bovine leukosis.